Effects of Essential Oils and Polyunsaturated Fatty Acids on Canine Skin Equivalents: Skin Lipid Assessment and Morphological Evaluation. (6th November 2013) - Cerrato, S.; Ramió-Lluch, L.; Fondevila, D.; Rodes, D.; Brazis, P.; Puigdemont, A.
Abstract : A canine skin equivalent model has been validated for the assessment of a topical formulation effects. Skin equivalents were developed from freshly isolated cutaneous canine fibroblasts and keratinocytes, after enzymatic digestion of skin samples (n = 8 ) from different breeds. Fibroblasts were embedded into a collagen type I matrix, and keratinocytes were seeded onto its surface at air-liquid interface. Skin equivalents were supplemented with essential oils and polyunsaturated fatty acid formulation or with vehicle. Skin equivalents were histopathologically and ultrastructurally studied, and the three main lipid groups (free fatty acids, cholesterol, and ceramides) were analyzed. Results showed that the culture method developed resulted in significant improvements in cell retrieval and confluence. Treated samples presented a thicker epidermis with increased number of viable cell layers, a denser and compact stratum corneum, and a more continuous basal membrane. Regarding lipid profile, treated skin equivalents showed a significant increase in ceramide content (51.7 ± 1.3 ) when compared to untreated (41.6 ± 1.4 ) samples. Ultrastructural study evidenced a compact and well-organized stratum corneum in both treated and control skin equivalents. In conclusion, cell viability and ceramides increase, after lipid supplementation, are especially relevant for the treatment of skin barrier disruptions occurring in canine atopic dermatitis.